The Role of NGF and Its Receptor TrKA in Patients With Erectile Dysfunction - Stabile, Anna Maria; Illiano, Ester; Pistilli, Alessandra; Rende, Mario; Trama, Francesco; Bartolini, Desiree; Zucchi, Alessandro; Costantini, Elisabetta (Frontiers in Urology, 2022)
The aim of our study was to investigate the plasma NGF concentration and TrkA/p75NTR receptor expression on white blood cells (WBCs), in peripheral and corpus cavernosum blood isolated from patients with erectile dysfunction and metabolic syndrome (ED/MetS). This was a pilot case–control study. Inclusion criteria were as follows: men 18–65 years with ED and MetS and healthy subjects. The first sampling was performed at the level of the cubital vein (VC). Subsequently, 20 μg of intracavernous alprostadil was administered, and a second blood draw from the corpora cavernosa (CC) was performed once erection was achieved. Subsequently, the third blood sample was repeated at the level of the VC. We enrolled 8 cases with ED/MetS and 8 controls. There was no significant difference between the case and control group in terms of mean age (49.3 ± 5.9 and 53.13 ± 8.9, respectively). The case group had a lower IIEF score compared to the control group (14 ± 3.2 versus 27.3 ± 2.1; p < 0.05). Decreased NGF and TrKA expression on WBC and thiols were found in the plasma of ED/MetS patients compared to control. The study showed that patients with ED/MetS had a decrease in plasma NGF and thiol concentration, and they had a decrease in TrKA expression on WBCs.